Cross Street at Haymarket Square, November 29, 1933 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northeast of Cross Street from Haymarket Square looking towards the intersection of Cross and Endicott Streets. Partially-demolished buildings line the southeast side of Cross Street between Haymarket Square to the southwest and Endicott Street to the northeast. Buildings lining the northwest side of Cross Street remain intact. Partially demolished buildings located at the northeast corner of Endicott and Cross Streets are included in the center-left portion of the photograph. Automobiles and pedestrians are included in the photograph. Street railroad tracks run along Washington Street at Haymarket Square and are visible near the bottom side of the photograph. Photographs